2023
DOI: 10.3389/fpsyg.2023.1061813
|View full text |Cite
|
Sign up to set email alerts
|

Social trust and the location choices of foreign firms in China–The moderating role of formal institution and cultural distance

Abstract: The institutional environment has a significant impact on the location of overseas investments by multinational enterprises (MNEs). However, there remain two research gaps. First, fewer studies focused on the impact of subnational regional institutions on the location choices of MNEs. Second, study on informal institutions has been more limited. This study investigates the effect of the informal institution (social trust) in the Chinese subnational region on the location choices of foreign firms and the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
(183 reference statements)
1
2
0
Order By: Relevance
“…Consequently, this would lessen the disadvantage they face in their host countries. Finally, in international business literature, several recent studies have begun to focus on the joint effect of formal and informal institutions (Shen et al, 2023). The results of our study are consistent with this and call for institutional complementarity in the support to be offered to immigrant entrepreneurs.…”
Section: Practical Implicationssupporting
confidence: 88%
“…Consequently, this would lessen the disadvantage they face in their host countries. Finally, in international business literature, several recent studies have begun to focus on the joint effect of formal and informal institutions (Shen et al, 2023). The results of our study are consistent with this and call for institutional complementarity in the support to be offered to immigrant entrepreneurs.…”
Section: Practical Implicationssupporting
confidence: 88%
“…This view is consistent with some previous research, for example, Papageorgiadis et al (2020) found that an informal institution related to intellectual property enforcement positively moderates the effect of formal law (intellectual property law) on foreign direct investment flows, indicating a complementary effect between the two in attracting foreign direct investment. Similarly, Shen et al (2023) found that social trust and formal institutions have a complementary effect in attracting foreign direct investment. Thus, we propose the following hypothesis.…”
Section: 4mentioning
confidence: 94%
“…Conversely, under conditions of low social trust, opportunism is likely to occur in economic exchanges, leading to additional uncertainty and transaction costs (Shen et al, 2023;Chen and Wu, 2023). Meanwhile, firms have difficulty in accessing local resources and are vulnerable to penalties from the host government and other stakeholders for violating institutional rules (Zhang and Beamish, 2019).…”
Section: Social Trust and Entry Modementioning
confidence: 99%